OP5 Pericoronary adipose tissue density is greater in takayasu arteritis than atherosclerosis and is associated with coronary arterial inflammation measured by 68Ga-DOTATATE PET. (7th September 2020) - Wall, Christopher; Huang, Yuan; Uy, Christopher; Le, Elizabeth PV; Tombetti, Enrico; Manavaki, Roido; Dweck, Marc R; Gopalan, Deepa; Bennett, Martin R; Slomka, Piotr; Dey, Damini; Mason, Justin C; et al.
Abstract : Introduction: Pericoronary adipose tissue (PCAT) density is associated with vascular inflammation, but its nature is not fully understood. We compared PCAT density with clinical and molecular imaging markers of inflammation. Methods: PCAT density was quantified in patients with Takayasu arteritis (TAK), coronary artery disease (CAD), and age and gender-matched healthy controls from cardiac CT images using semi-automated software (Autoplaque). In TAK patients, PCAT density was also compared to the Indian Takayasu Clinical Activity Score (ITAS). In CAD patients, PCAT density was compared to maximum tissue-to-blood ratio (TBRmax ) from motion-corrected 68 Ga-DOTATATE PET, using image registration software (FusionQuant), and aortic 18 F-fluorodeoxyglucose (FDG) PET. Imaging was acquired during clinical care or prior research. 68 Ga-DOTATATE is an experimental marker of vascular inflammation that binds macrophage somatostatin receptor-2. Results: 60 patients were included (TAK, n=20; CAD, n=20; healthy, n=20). Mean PCAT density varied significantly among the three groups (TAK: -74.00 ±SD 11.92 Hounsfield unit [HU]; CAD: -80.39 ±SD 10.9 HU; healthy controls: -83.85 ±SD 10.07 HU; p<0.0001). C-reactive protein was greater in TAK than CAD patients (TAK: 25.2 ±SD 16.1 mg/L; CAD: 2.5 ±SD 1.73 mg/L, p=0.04). PCAT density was significantly associated with ITAS (r=0.61, p=0.004) in TAK patients, and coronary 68 Ga-DOTATATE TBRmax (rho=0.31, p<0.001) in CAD patients. No significant patient-level confounders were identified. PCAT density was not statistically associated with aortic 18 F-FDG in CAD patients, or subcutaneous (pre-sternal) adipose tissue density in either disease group. Conclusion: PCAT density could be a useful, non-PET marker of coronary arterial inflammation and disease activity in both TAK and CAD patients.